Overprotective Parenting and Its Implications for Independent Character Development in University Students - Septiani, Salma Selly; Nurmasitah, Sita (Universitas Negeri Semarang, 2025)
This study investigates the influence of overprotective parenting on independent character development among out-of-town university students enrolled in a Home Economics Education Program. Independence in emerging adulthood encompasses emotional, behavioral, and value-based autonomy, essential for functioning as responsible adults. Using a quantitative approach with simple linear regression analysis, data were collected from 103 students selected through purposive sampling. The results show a negative relationship between overprotective parenting and student independence; however, the effect was not statistically significant (p = 0.744). These findings suggest that while overprotective parenting may inhibit autonomy to some extent, student independence is more significantly shaped by broader contextual factors such as peer interaction, campus engagement, and experiential learning. Peer interaction can provide opportunities for students to practice independence in a supportive environment, while campus engagement and experiential learning can foster autonomy by encouraging students to take initiative and make decisions. The study highlights the need for holistic strategies within higher education to foster independence beyond family influences alone. Implications of this study indicate that universities should create structured programs that support student autonomy and self-regulation. At the same time, future research is encouraged to explore mediating variables that may better explain the development of independence during emerging adulthood.